1999
DOI: 10.1110/ps.8.6.1200
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the structural boundaries of independent folding domains in the a subunit of tryptophan synthase, a β/α barrel protein

Abstract: Two equilibrium intermediates have previously been observed in the urea denaturation of the a subunit of tryptophan synthase~aTS! from Escherichia coli, an eight-stranded b0a barrel protein. In the current study, a series of aminoterminal fragments were characterized to probe the elementary folding units that may be in part responsible for this complex behavior. Stop-codon mutagenesis was used to produce eight fragments ranging in size from 105-214 residues and containing incremental elements of secondary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 51 publications
7
91
1
Order By: Relevance
“…We find that in 6 M GuHCl this value expands to 48.8 Ϯ 1.0 Å, consistent with random-coil predictions. This observation is also consistent with NMR-based reports that at concentrations above 6 M urea the protein undergoes an additional cooperative transition (36). In contrast, we observe an R G of 46 Ϯ 1.5 Å for creatine kinase in 6 M GuHCl, which is within error of previous reports (34) but significantly less than the 67 Å predicted for a 380-residue random coil.…”
Section: Resultssupporting
confidence: 92%
“…We find that in 6 M GuHCl this value expands to 48.8 Ϯ 1.0 Å, consistent with random-coil predictions. This observation is also consistent with NMR-based reports that at concentrations above 6 M urea the protein undergoes an additional cooperative transition (36). In contrast, we observe an R G of 46 Ϯ 1.5 Å for creatine kinase in 6 M GuHCl, which is within error of previous reports (34) but significantly less than the 67 Å predicted for a 380-residue random coil.…”
Section: Resultssupporting
confidence: 92%
“…Our simulations of a 16-residue ␤-hairpin peptide fragment from protein G (40) have shown that it folds rapidly and cooperatively to a conformation with a defined secondary structure and a packed hydrophobic cluster of aromatic side chains. In experiments, this peptide has been observed to be very stable (41).…”
Section: Discussionmentioning
confidence: 93%
“…By including the two types of terms, with respect to both fragment size and as a function of the fraction of the fragment size to the whole protein, we obtain a balance for all fragment sizes. To validate the success of our fragment-size-independent scoring function will require a set of systematically carried out stability measurements either from experiments (25,41) or from theoretical calculations (42) for protein fragments of different sizes. However, the consistency and the improvement of the HFU assignments via a combinatorial assembly of the assigned building blocks is an indirect evidence for its validity.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with analogous (ba) 6 fragments of both S. cerevisiae PRAI and the a subunit of tryptophan synthase, which show spectra of a similar shape but of much reduced intensity compared with the fulllength protein [23,33]. In even starker contrast with the (ba) 6 fragment from the yeast enzyme [23], the trPRAIHis near-UV spectrum is also of a similar form and magnitude to that of full-length PRAI.…”
Section: Biophysical Characterization Of Trpraimentioning
confidence: 70%
“…In the last five years, a substantial body of evidence has accumulated for the existence of autonomously folding subdomains in (ba) 8 -barrel proteins including triosephosphate isomerase [38,39], the (ba) 8 -barrels of histidine biosynthesis [40][41][42], IGPS [43], and the a subunit of tryptophan synthase [33,44]. Protein folding studies have suggested that PRAI folds through an intermediate consisting of (ba) 1)5 b 6 [34].…”
Section: -Barrelsmentioning
confidence: 99%